Coherent acoustic phonon oscillation accompanied with backward acoustic pulse below exciton resonance in a ZnO epifilm on oxide-buffered Si(1 1 1). (19th July 2016) - Lin, Ja-Hon; Shen, Yu-Kai; Liu, Wei-Rein; Lu, Chia-Hui; Chen, Yao-Hui; Chang, Chun-peng; Lee, Wei-Chin; Hong, Minghwei; Kwo, Jueinai-Raynien; Hsu, Chia-Hung; Hsieh, Wen-Feng
Abstract: Unlike coherent acoustic phonons (CAPs) generated from heat induced thermal stress by the coated Au film, we demonstrated the oscillation from c-ZnO epitaxial film on oxide buffered Si through a degenerate pump–probe technique. As the excited photon energy was set below the exciton resonance, the electronic stress that resulted from defect resonance was used to induce acoustic wave. The damped oscillation revealed a superposition of a high frequency and long decay CAP signal with a backward propagating acoustic pulse which was generated by the absorption of the penetrated pump beam at the Si surface and selected by the ZnO layer as the acoustic resonator.